Catalytic enantioselective desymmetrization of meso-aziridines. Issue 3 (12th December 2022) - Yang, Pei-Jun; Chai, Zhuo
Abstract : Over the past three decades, the catalytic enantioselective desymmetrization of meso -aziridines has evovled to be a ready synthetic toolkit for efficient construction of diverse useful nitrogen-containing molecules bearing contiguous stereocenters. Abstract : As a type of readily available small strained-ring heterocycle, meso -aziridines may undergo catalytic desymmetrizing transformations to empower the rapid construction of diverse nitrogen-containing structures bearing contiguous stereocenters, which have great relevance in natural product synthesis, drug development and the design and synthesis of chiral catalysts/ligands for asymmetric catalysis. This review outlines the advances achieved in the catalytic asymmetric desymmetrization of meso aziridines and highlights some promising avenues for further work in this realm.